FEATURES ENZYME COMPOSITION BLOOD SERUM OF RATS BEARING GUERIN CARCINOMA UPON AND USE OF FRUIT-BERRY EXTRACT FOUGO - Фуджу Халід Ісса Мохамед, (World of Medicine and Biology, 2013)
The study of features of the enzyme serum of rats carcinoma growth and use of fruit extract Fuji. We determined serum enzyme composition of animals in terms alanine aminotransferase, aspartate aminotransferase, hamahlutamiltranferazy, lactate dehydrogenase and alkaline phosphatase. Found that the maximum violation of the enzyme spectrum in blood serum were observed on the 14 th and 21-st day.
Keywords: fruit and berry extract Fougo; Guerin carcinoma; enzymatic composition of blood serum